Key Dynamics of Internationalization of Public Policy in the Context of Policy Transfer - Nainggolan, Alexander Hamonangan (Jurnal Politik, 2017)
The article aims at examining how policy could be transferred as a complex and dynamic process in terms of internationalization and globalization. In addition, it will explore significant channels for the international movement of ideas, policies, and practices through an international policy learning process formed in policy transfer, lesson drawing, policy diffusion, and policy convergence. Further, it is argued that policy transfer literature is increasingly central, leading to the development of related topics in comparative politics and public policy. This article investigates the involvement of non-government organizations, civil society and political issues in driving the learning process about what government should have done and can be learned with common problems. Finally, the article concludes that globalization has challenged the notion of a nation-state system and the autonomy of nation-states by the velocity of change and the dynamic of interstate and intrastate factors in term of policy transfer.